Hubungan Tingkat Pengetahuan Ibu Hamil Dan Dukungan Suami Dengan Motivasi Pemeriksaan Antenata Care Dipuskesmas Sungai Raya Dalam - Tutur Kardiatun; Lidia Hastuti; Yenni Lukita; Irham Irham (Jurnal Keperawatan dan Kesehatan, 2014)
Background: Each year approximately 20,000 women die from complications in Indonesia in persalinan.One of them to reduce the "maternal death." One of them by increasing the knowledge and support of her husband and motivation so that pregnant women can be examined pregnancy appropriate and timely manner . Objective: This study aims to determine the "relationship between maternal knowledge and support of her husband on the motivation of antenatal care (ANC). Methods: This type of study design using analytic observational study with cross sectional approach to study the relationship between maternal knowledge and support of her husband on the motivation of antenatal care (ANC). The design is a cross sectional analytical study design aimed to determine the relationship of the independent variables are variables where the knowledge and support of her husband and the dependent variable motivation diidenfikasi on one unit waktu.analisa ches quare test data using the (α) = 0.05 . Results of the study: from the analysis there was a significant association between maternal knowledge and motivation antenatal care (Ha accepted) (p = 0.026 ≤ 0.05) and no significant relationship between husband and motivational support antenatal care (Ha rejected) higher value of (p = 0.321 ≥ 0.05). Conclusion: there is a relationship between knowledge of pregnant women with antenatal care in motivation that could mean that the knowledge of factors can affect the motivation of pregnant women in antenatal care , while there was no relationship with the husband's support motivation antenatal care it can be interpreted that the husband's support factor can not affect the motivation of prenatal care .